Disaster Debris: Fire in the Largo do Paissandú-SP, 2018 - de Brito Junior, Irineu [UNESP]; Freire, Larissa Ciccotti; Bertazzo, Tábata Rejane; de Andrade Santos, Filipe Aécio Alves; Yoshizaki, Hugo Tsugunobu Yoshida (Springer Nature, 2020)
This study presents the management of over 5000 tons of debris generated in the fire in Largo do Paissandú, São Paulo/Brazil, 2018. The process lasted 12 days and the debris was sent to a construction and demolition landfill without prior segregation, not abiding by the best practices in disaster waste recovery.
Keywords: Disaster; Disaster waste management; Donation; Humanitarian logistics